Solanum chippendalei Symon, Citrus glauca (Lindl.) Burkill, Ficus racemosa L. and Melaleuca alternifolia Cheel Inhibit Axillary and Foot Odour Producing Bacteria - Baghtchedjian, Linn; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Plant-based preparations have potential to replace synthetic antiperspirant/ deodorant additives as growth inhibitors of malodour producing bacteria and may thus be useful deodorant components. However, relatively few plant species have yet been tested against the bacteria. Materials and Methods: Methanolic S. chippendalei and C. glauca fruit extracts, as well as F. racemosa and M. alternifolia leaf extracts were investigated by disc diffusion and liquid dilution MIC assays against the most significant bacterial contributors to axillary and plantar malodour. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: All of the tested extracts inhibited the growth of two or more bacteria, although the MIC values measured for the C. glauca fruit and F. racemosa leaf extracts indicated only weak antibacterial activity. In contrast, the M. alternifolia leaf extract displayed noteworthy growth inhibitory activity against all of the malodour forming bacteria tested, with liquid dilution (LD) MIC values of 1667, 1230, 1250 and 2720 μg/mL against C. jeikeium, C. acnes, B. linens and S. epidermidis respectively. Interestingly, the S. chippendalei fruit extract was the strongest inhibitor of C. jeikeium growth (MIC=1070 μg/mL), although it was substantially less potent against the other bacterial species. All extracts were nontoxic in the Artemia fransiscana bioassay. Conclusion: The lack of toxicity of the S. chippendalei, C. glauca, F. racemosa and M. alternifolia extracts and growth inhibition of axillary and plantar malodour producing bacteria by the S. chippendalei fruit and M. alternifolia leaf extracts indicate their potential as deodorant components. Further studies are warranted to isolate and identify the active components.
Keywords: Australian plants; Body odour; Deodorant; Corneybacterium jeikeium; Propionobacter acnes; Brevibacter linens; Staphylococcus epidermidis.